2019
DOI: 10.5505/anatoljfm.2019.66375
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Brenner tumor of the ovary: one single institute experience and a review of the literature

Abstract: Malignant Brenner tumors (MBT) of the ovary are rare diseases, representing 1% of all ovarian cancers and 3-5% of Brenner tumors. They carry a poor prognosis. They generally affect women during the perimenopausal and postmenopausal periods. The standard treatment is surgery; however, the indication of adjuvant chemotherapy remains controversial. The present study aims to report our experience in the treatment of MBT of the ovary, to better characterize this disease. Methods: In this study, a retrospective case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…This subtype was first described by Fritz Brenner in 1907 [ 1 , 4 ]. The exact incidence of malignant Brenner tumor (MBT) is not known.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This subtype was first described by Fritz Brenner in 1907 [ 1 , 4 ]. The exact incidence of malignant Brenner tumor (MBT) is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical manifestations are often nonspecific and may resemble other ovarian tumors, thus causing a delay in diagnosis. Symptoms usually become more visible in advanced stages (stage III or stage IV) [ 4 6 ]. Bouhani et al [ 4 ] reported 4 cases of Brenner tumor, which all had nonspecific initial symptoms such as abdominal distention, abdominal pain, pelvic mass, and pelvic pain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations